Silicon-carbon negative electrode material and preparation method and application thereof

By combining nanosilicon and graphite sheets in the lithium-ion battery negative electrode material using electrostatic action and double-layer coating of graphene carbon and titanium dioxide, the conductivity and expansion problems of silicon materials are solved, and a silicon-carbon negative electrode material with high specific capacity and long cycle stability is achieved.

CN119833591APending Publication Date: 2025-04-15NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411733233.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

As the negative electrode material of lithium-ion batteries, silicon has poor intrinsic conductivity and severe volume expansion problems, resulting in cracking of the electrode material, losing electrochemical properties, and forming an unstable SEI film, affecting the long cycle performance.

Method used

Through electrostatic action, the nano-silicon and graphite sheet are closely combined to form a core, and double-layered coating is carried out on its outer surface: graphene carbon coating and titanium dioxide coating, which inhibits the volume expansion and side reaction of silicon and enhances electrochemical stability.

Benefits of technology

The high specific capacity, low volume expansion and good long cycle stability of silicon-carbon anode material are achieved, which improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833591A_ABST
    Figure CN119833591A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. The silicon-carbon negative electrode material comprises an inner core and double coating layers, nanometer silicon and graphite sheets are tightly combined through electrostatic interaction to form the inner core, and the outer surface of the inner core is sequentially coated with a graphene carbon coating layer and a titanium dioxide coating layer from inside to outside. The nanometer silicon and the graphite flake in the inner core of the silicon-carbon negative electrode material are tightly combined through electrostatic interaction, so that the stability of the inner core is enhanced, and the conductivity of the negative electrode material is also enhanced; the graphene carbon coating layer and the titanium dioxide coating layer are used as protective shells to inhibit volume expansion of silicon and ensure good contact between nano silicon and graphite flakes, so that side reactions are reduced; through the synergistic effect of the inner core and the double coating layers, the silicon-carbon negative electrode material has high specific capacity, good cycle performance and high capacity retention rate. The preparation method is simple, raw materials are easy to obtain, cost is low, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of society and the progress of the times, people's requirements for the new energy industry are also constantly increasing. Lithium-ion batteries, as representatives of secondary batteries, have been widely used, and their traditional graphite anodes can no longer meet the needs of modern society due to the limitation of theoretical capacity (372 mAh / g). Silicon has become an ideal choice for the development of high-energy-density battery anode materials because of its advantages such as high theoretical capacity (4200 mAh / g), low lithium insertion potential (0.5 V), and sufficient reserves. Although silicon has such a high theoretical capacity, it still faces many problems in practical applications: silicon has poor intrinsic conductivity, and severe volume expansion during lithium removal and lithium insertion causes the electrode material to crack and break, fall off from the current collector and lose electrochemical properties; at the same time, repeated expansion and contraction lead to the formation of an unstable SEI film, and the surface side reactions continuously consume the electrolyte, resulting in poor long-cycle performance of silicon anode materials. Therefore, the preparation of a silicon-based anode material with low expansion and long cycle performance has become the focus and difficulty of research and development in the battery anode material industry. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a silicon-carbon negative electrode material and a preparation method and application thereof, wherein the silicon-carbon negative electrode material has high specific capacity, low volume expansion and good long cycle stability.

[0004] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a silicon-carbon negative electrode material, which has a core and a double coating layer. Nano-silicon and graphite sheets are tightly combined through electrostatic action to form the core, and the outer surface of the core is sequentially coated with a graphene carbon coating layer and a titanium dioxide coating layer from the inside to the outside.

[0005] In the silicon-carbon negative electrode material provided by the present invention, nano silicon and graphite sheets are closely combined through electrostatic action, which enhances the stability of the core and the conductivity of the negative electrode material; graphene carbon is used as the first coating layer, which not only anchors nano silicon on the surface of the graphite sheet, enhances the electrical contact between nano silicon and the graphite sheet, but also acts as a protective shell to inhibit the volume expansion of silicon; titanium dioxide is deposited in situ on the surface of the first coating layer as the second coating layer, and titanium dioxide has high strength, which can effectively inhibit the expansion of nano silicon, and the stable outer surface effectively reduces the occurrence of side reactions, and the lithium-treated titanium dioxide can quickly transmit lithium ions. Through the synergistic effect of the double coating of the graphene carbon layer and the titanium dioxide layer, the volume expansion of silicon in the charge and discharge cycle is inhibited, and the formation of a stable SEI film is promoted. The unique composite structure enables the silicon-carbon negative electrode material to have a high specific capacity and low volume expansion while having good long-cycle performance.

[0006] In a second aspect, the present invention also provides a method for preparing the above silicon-carbon negative electrode material, comprising the following steps: S1, adding cationic surfactant to the aqueous solution of nano-silicon, stirring evenly, centrifuging, washing with water and drying to obtain modified nano-silicon; acidifying, washing with water, washing with alcohol and drying the graphite sheet to obtain the modified graphite sheet; S2, the modified nano-silicon in step S1 is dispersed in water to obtain a nano-silicon dispersion; the modified graphite flakes in step S1 are dispersed in water, and a non-ionic surfactant is added to obtain a graphite flake dispersion; the nano-silicon dispersion is added dropwise to the graphite flake dispersion to obtain a mixed solution; the mixed solution is centrifuged and dried to obtain a silicon-carbon mixed powder; S3, the silicon-carbon mixed powder described in step S2 is subjected to chemical vapor deposition in an atmosphere containing a carbon source and an inert gas to obtain a silicon-carbon precursor having a graphene carbon coating layer; S4. Add the silicon-carbon precursor described in step S3 to a mixed solution in which the volume ratio of anhydrous ethanol and ammonia water is 100:(0.1-10), and add tetrabutyl titanate solution after uniform dispersion. After aging, centrifugation and drying in sequence, annealing treatment is performed under an inert atmosphere to obtain a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer.

[0007] The present invention provides a method for preparing a silicon-carbon negative electrode material. The method comprises the following steps: firstly, nano-silicon is modified by a strong cationic surfactant to make it positively charged, and then the negative charge of a graphite sheet is enhanced by acidification. The two are tightly combined due to the electrostatic effect, and then double-layer coating is performed. The first layer of graphene carbon coating is performed by a chemical vapor deposition method. The graphene carbon formed at a high temperature is used as the first coating layer, which not only anchors the nano-silicon on the surface of the graphite sheet and forms a good electrical contact between the nano-silicon and the graphite sheet, but also acts as a protective shell to inhibit the volume expansion of silicon. The second layer of titanium dioxide coating is performed by a sol-gel method. Titanium dioxide is in-situ deposited on the surface of the first coating layer as the second coating layer. The rigid structure of titanium dioxide inhibits the expansion of nano-silicon, and the stable outer surface reduces the occurrence of side reactions. Moreover, the lithium-treated titanium dioxide has excellent lithium ion conductivity. The method for preparing the silicon carbide negative electrode material is simple, low-cost, and suitable for industrial production.

[0008] In a possible implementation, the particle size of the nano silicon in step S1 is 50 to 500 nm. By controlling the particle size of the nano silicon within the range of 50 to 500 nm, the occurrence of cracking in the prepared silicon-carbon negative electrode material can be reduced.

[0009] In a possible implementation, the cationic surfactant in step S1 includes one or more of polydiallyldimethylammonium chloride, polyethyleneimine, polyvinylamine and polyvinylpyridine. The above cationic surfactant is a strong cationic surfactant that can make the surface of nano-silicon carry abundant positive charges.

[0010] In a possible implementation, the acidification in step S1 uses sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is (0.02-4): 1. By using a combination of sulfuric acid and nitric acid and controlling the usage ratio of the two, the graphite sheet can be sufficiently negatively charged while avoiding the damage to the graphite sheet caused by sulfuric acid and nitric acid during the acidification process and the safety problems caused by strong acid.

[0011] In a possible implementation, the acidification temperature in step S1 is 60-90° C. Acidification at 60-90° C. is beneficial to increase the acidification rate and make the reaction more complete.

[0012] In a possible implementation, the nonionic surfactant in step S2 includes one or more of polyoxyethylene derivatives, alkyl alcohol amides, polyol monofatty acid esters, alkyl amine oxides, and N-methylpyrrolidone. The use of the above nonionic surfactants can make the graphite flakes more evenly dispersed.

[0013] In a possible implementation manner, the mass ratio of the modified nano-silicon and the modified graphite sheet in step S2 is (0.2 to 5): 1. By controlling the usage ratio of the modified nano-silicon and the modified graphite sheet, it is more conducive to achieving a balance between high specific capacity and high cycle stability of the silicon-carbon negative electrode material.

[0014] In a certain possible implementation manner, the carbon source in step S3 includes one or more of acetylene, methane, ethylene and camphor. The above carbon sources can form a graphene carbon coating layer at high temperature.

[0015] In a possible implementation manner, the inert gas in step S3 includes one or both of argon and nitrogen.

[0016] In a possible implementation, the flow ratio of the carbon source to the inert gas in step S3 is (0.1-2):1, and the temperature of the chemical vapor deposition is 900-1200°C and the time is 10-300 min. By controlling the process parameters of the chemical vapor deposition, a graphene carbon coating layer of suitable thickness is obtained while obtaining the graphene carbon coating layer, which is more conducive to achieving a balance between high specific capacity and high cycle stability of the silicon-carbon negative electrode material.

[0017] In a possible implementation, the mass ratio of the silicon-carbon precursor to the tetrabutyl titanate in step S4 is 1:(0.1-10), and the temperature of the annealing treatment is 200-800° C. By controlling the mass ratio of the silicon-carbon precursor to the tetrabutyl titanate and the temperature of the annealing treatment, a titanium dioxide coating layer of suitable thickness and structure can be obtained, which is more conducive to achieving a balance between high specific capacity and high cycle stability of the silicon-carbon negative electrode material.

[0018] In a third aspect, the present invention also provides the application of the above silicon-carbon negative electrode material in the field of lithium-ion batteries.

[0019] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.

[0020] The reagents and raw materials used in the present invention are commercially available.

[0021] The positive and progressive effects of the present invention are: The silicon-carbon negative electrode material provided by the present invention has nano-silicon and graphite sheets in the core tightly combined by electrostatic action, which enhances the stability of the core while the graphite sheets also enhance the conductivity of the material; the graphene carbon coating layer formed at high temperature fixes the nano-silicon on the surface of the graphite sheet, ensuring good contact between the nano-silicon and the graphite sheet, and the graphene carbon coating layer also acts as a protective shell to inhibit the volume expansion of silicon; while the titanium dioxide coating layer inhibits the volume expansion of silicon, its stable outer surface also reduces the occurrence of side reactions; through the synergistic effect of the core and the double-layer coating layer, the silicon-carbon negative electrode material has high specific capacity, good cycle performance and high capacity retention rate. The preparation method of the silicon-carbon negative electrode material provided by the present invention is simple, the raw materials are easily available, the cost is low, it is suitable for industrial production, and has broad application prospects in the field of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the silicon-carbon negative electrode material prepared in Example 1.

[0023] Figure 2 The silicon-carbon negative electrode material prepared in Example 1 is 0.1 A g -1 First cycle charge and discharge curves under current density.

[0024] Figure 3 The silicon-carbon negative electrode material prepared in Example 1 is 1 A g -1 Coulombic efficiency and cycling performance after 50 cycles at the same current density. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0026] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0027] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0028] Example 1

[0029] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 200 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Pass argon gas in a tube furnace with a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and hold for 30 min. Then, pass 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0030] Figure 1 This is a scanning electron microscope image of the silicon-carbon negative electrode material prepared in Example 1. It can be seen from the image that the silicon carbide negative electrode material has a micron-scale flaky morphology.

[0031] The silicon-carbon negative electrode material prepared in Example 1 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 The current density is tested for long term cycling. Figure 2 and Figure 3 At 100 mA g -1 At the current density, the discharge capacity is 1176.4 mAh g -1 , the first efficiency is 84.2%, at 1 A g -1 At the current density, the capacity retention rate was 86.3% after 50 charge and discharge cycles.

[0032] Example 2

[0033] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 200 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Pass argon gas in a tube furnace with a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and hold for 30 min. Then, pass 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 0.5 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0034] The silicon-carbon negative electrode material prepared in Example 2 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1376.5 mAh g -1 , the first efficiency is 82.7%, at 1 A g -1 At the current density, the capacity retention rate was 88.8% after 50 charge and discharge cycles.

[0035] Example 3

[0036] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 200 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Pass argon gas in a tube furnace with a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and hold for 30 min. Then, pass 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1.5 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0037] The silicon-carbon negative electrode material prepared in Example 3 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1110.8 mAh g -1 , the first efficiency is 79.5%, at 1 A g -1 At the current density, the capacity retention rate was 81.6% after 50 charge and discharge cycles.

[0038] Example 4

[0039] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 200 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Introduce argon gas in a tube furnace at a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and maintain for 30 min. Then, introduce 100 sccm of methane for deposition for 50 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0040] The silicon-carbon negative electrode material prepared in Example 4 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1055.2 mAh g -1 The first efficiency is 85.7% at 1 A g -1 At the current density, the capacity retention rate was 88.5% after 50 charge and discharge cycles.

[0041] Example 5

[0042] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 300 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the obtained uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Pass argon gas in a tube furnace with a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and hold for 30 min. Then, pass 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0043] The silicon-carbon negative electrode material prepared in Example 5 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1755.2 mAh g -1 , the first efficiency is 84.9%, at 1 A g -1 At the current density, the capacity retention rate was 84.1% after 50 charge and discharge cycles.

[0044] Example 6

[0045] (1) Disperse 0.5 g of nano-silicon powder with a particle size of 100 nm in 100 mL of deionized water, ultrasonicate for 1 h, add 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride dropwise, stir for 2 h, centrifuge, wash three times with water and dry to obtain modified nano-silicon; assemble a reflux device, add 1 g of exfoliated graphite flakes, 25 ml of sulfuric acid and 75 ml of nitric acid in a round-bottom flask in sequence, place the flask in an oil bath, heat to 80 °C and stir for 3 h, wash the acidified exfoliated graphite flakes with water three times, alcohol three times and dry to obtain modified exfoliated graphite flakes; (2) dispersing 200 mg of the modified nanosilicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nanosilicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a nonionic surfactant, polyethyleneimine, stirring to obtain a nanosilicon dispersion; adding the nanosilicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Pass argon gas in a tube furnace with a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and hold for 30 min. Then, pass 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0046] The silicon-carbon negative electrode material prepared in Example 6 was assembled into a button cell, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1125.2 mAh g -1 , the first efficiency is 84.6%, at 1 A g -1 At the current density, the capacity retention rate was 86.4% after 50 charge and discharge cycles.

[0047] Comparative Example 1 0.5 g of nano-silicon powder with a particle size of 100 nm was dispersed in 100 mL of deionized water and ultrasonicated for 1 h. 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride was added dropwise. After stirring for 2 h, the mixture was centrifuged, washed three times with water and dried to obtain modified nano-silicon. 500 mg of powder was weighed and placed in a porcelain boat. Argon was introduced into a tubular furnace with a flow rate of 100 sccm. The temperature was raised to 400 °C at a rate of 5 °C / min and maintained for 30 min. After cooling, the modified nano-silicon negative electrode material was obtained.

[0048] The modified nano-silicon negative electrode material prepared in Comparative Example 1 was assembled into button cells, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 3568.8 mAh g -1 , the first efficiency is 90.2%, at 1 A g -1 At the current density, the capacity retention rate was 9.85% after 50 charge and discharge cycles.

[0049] Comparative Example 2 (1) 0.5 g of nano-silicon powder with a particle size of 100 nm was dispersed in 100 mL of deionized water, ultrasonicated for 1 h, 5 ml of strong cationic surfactant polydiallyldimethylammonium chloride was added dropwise, stirred for 2 h and then centrifuged. The mixture was washed three times with water and dried to obtain modified nano-silicon; (2) dispersing 200 mg of the modified nano-silicon prepared in step (1) in 50 ml of deionized water, stirring to obtain a nano-silicon dispersion; dispersing 400 mg of the modified exfoliated graphite flakes prepared in step (1) in 100 ml of deionized water, adding 200 mg of a non-ionic surfactant, N-methylpyrrolidone, stirring to obtain a nano-silicon dispersion; adding the nano-silicon dispersion dropwise to the graphite flake dispersion, placing the mixed solution on a stirrer and stirring to obtain a uniformly mixed solution; centrifuging the uniformly mixed solution, and vacuum drying to obtain a mixed powder; (3) Weigh 500 mg of the mixed powder of step (2) and place it in a porcelain boat. Introduce argon gas in a tube furnace at a flow rate of 100 sccm. Raise the temperature to 1050 °C at a rate of 5 °C / min and maintain for 30 min. Then, introduce 100 sccm of methane for deposition for 30 min. After cooling, obtain a silicon-carbon precursor. (4) The silicon-carbon precursor prepared in step (3) is coated with titanium dioxide. 0.5 ml of ammonia water is added to 50 ml of anhydrous ethanol. After mixing evenly, 500 mg of the silicon-carbon precursor is added. The mixed solution is placed on a stirrer for heating and stirring. 1 ml of tetrabutyl titanate solution is added dropwise. After aging for 12 h, the mixture is centrifuged and dried. The mixture is heated to 400 °C at a rate of 5 °C / min in an argon atmosphere with a flow rate of 100 sccm and maintained for 30 min. After cooling, a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer is obtained.

[0050] The silicon-carbon negative electrode material prepared in Comparative Example 2 was assembled into button cells, and the battery charge and discharge cycle test was carried out using a blue power system at 100 mA g -1 After 5 cycles of activation with a current density of 1 A g -1 Long-term cycle test was carried out at 100 mA g -1 At the current density, the discharge capacity is 1164.1 mAh g -1 , the first efficiency is 81.8%, at 1 A g -1 At the current density, the capacity retention rate is 80.85% after 50 charge and discharge cycles.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a core and a double coating layer. Nano silicon and graphite sheets are tightly combined by electrostatic action to form the core. The outer surface of the core is sequentially coated with a graphene carbon coating layer and a titanium dioxide coating layer from the inside to the outside.

2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: S1, adding cationic surfactant to the aqueous solution of nano-silicon, stirring evenly, centrifuging, washing with water and drying to obtain modified nano-silicon; acidifying, washing with water, washing with alcohol and drying the graphite sheet to obtain the modified graphite sheet; S2, the modified nano-silicon in step S1 is dispersed in water to obtain a nano-silicon dispersion; the modified graphite flakes in step S1 are dispersed in water, and a non-ionic surfactant is added to obtain a graphite flake dispersion; the nano-silicon dispersion is added dropwise to the graphite flake dispersion to obtain a mixed solution; the mixed solution is centrifuged and dried to obtain a silicon-carbon mixed powder; S3, the silicon-carbon mixed powder described in step S2 is subjected to chemical vapor deposition in an atmosphere containing a carbon source and an inert gas to obtain a silicon-carbon precursor having a graphene carbon coating layer; S4. Add the silicon-carbon precursor described in step S3 to a mixed solution in which the volume ratio of anhydrous ethanol and ammonia water is 100:(0.1-10), and add tetrabutyl titanate solution after uniform dispersion. After aging, centrifugation and drying in sequence, annealing treatment is performed under an inert atmosphere to obtain a silicon-carbon negative electrode material having a titanium dioxide coating layer and a graphene carbon coating layer.

3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The particle size of the nano-silicon in step S1 is 50 to 500 nm; And / or, the cationic surfactant in step S1 includes one or more of polydiallyldimethylammonium chloride, polyethyleneimine, polyvinylamine and polyvinylpyridine.

4. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The acidification in step S1 adopts sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is (0.02 ~ 4):1; And / or, the acidification temperature in step S1 is 60-90°C.

5. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The nonionic surfactant in step S2 includes one or more of polyoxyethylene derivatives, alkyl alcohol amides, polyol monofatty acid esters, alkyl amine oxides and N-methylpyrrolidone.

6. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The mass ratio of the modified nano-silicon to the modified graphite sheet in step S2 is (0.2 ~ 5):

1.

7. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The carbon source in step S3 includes one or more of acetylene, methane, ethylene and camphor; And / or, the inert gas in step S3 includes one or both of argon and nitrogen.

8. The method for preparing the silicon-carbon negative electrode material according to claim 2 or 7, characterized in that: In step S3, the flow ratio of the carbon source to the inert gas is (0.1-2):1, the temperature of the chemical vapor deposition is 900-1200°C, and the time is 10-300 min.

9. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: In step S4, the mass ratio of the silicon-carbon precursor to the tetrabutyl titanate is 1:(0.1-10), and the temperature of the annealing treatment is 200-800°C.

10. Application of the silicon-carbon negative electrode material as claimed in claim 1 in the field of lithium-ion batteries.

Citation Information

Cited By

  • Silicon-carbon negative electrode material applied to sulfide solid-state battery and modification method of silicon-carbon negative electrode material

    CN120237195A

  • Preparation method and application of silicon-carbon negative electrode material based on two-step liquid-phase electrostatic self-assembly

    CN120473496A

  • Double-layer coated spherical composite material, preparation method thereof and application of double-layer coated spherical composite material in lithium ion battery

    CN120565608A

  • Composite silicon carbon electrode material and preparation method thereof

    CN120978053A